Studi Kasus :Pengaruh Akupresur Titik P6 Dan St36 Pada Pasien Kanker Dengan Nausea - Kharisna, Dendy; Saharudin, Saharudin; Putra, Ifon Dwiposwana; SS, Tison (Yayasan Healing and Healthcare Education, 2025)
Nausea and vomiting are common side effects that plague cancer patients during chemotherapy, risking anorexia, dehydration, electrolyte disturbances and decreased quality of life. The treatment can be done pharmacologically and nonpharmacologically, one of which is acupressure at points P6 and ST36. This study aims to determine the effectiveness of acupressure in reducing nausea in cancer patients undergoing chemotherapy. The study was conducted in the Tulip room of Arifin Achmad Hospital, Riau Province in July 2025 with a pre-test and post-test design involving one cancer patient who received the intervention for three consecutive days within ±1-2 minutes. The results showed a significant reduction in the level of nausea based on the Indonesian Nursing Outcome Standards (SLKI). The Numeric Rating Scale (NRS) score showed a decrease from 4 (moderate) to 2 (mild). Other symptoms such as urge to vomit, decreased appetite, and pallor also improved after the intervention. These findings support the use of acupressure as an effective nonpharmacological complementary therapy, and are recommended to be considered in nursing practice, whether performed independently by patients or with the help of health workers.